2016
DOI: 10.1016/j.jhep.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of epithelial to mesenchymal transition in hepatocellular carcinoma

Abstract: The epithelial to mesenchymal transition (EMT) is a multistep biological process whereby epithelial cells change in plasticity by transient de-differentiation into a mesenchymal phenotype. EMT and its reversal, mesenchymal to epithelial transition (MET), essentially occur during embryogenetic morphogenesis and have been increasingly described in fibrosis and cancer during the last decade. In carcinoma progression, EMT plays a crucial role in early steps of metastasis when cells lose cell-cell contacts due to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
415
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(439 citation statements)
references
References 116 publications
23
415
0
1
Order By: Relevance
“…The growth and metastasis of a tumor depends on its own vascular network. Apart from the vessel tunnels, which are lined with endothelial cells, Maniotis et al found a new microcirculation mechanism: channels are externally lined with tumor cells, with no endothelial cells in human melanoma [5]. This phenomenon has been termed vasculogenic mimicry (VM).…”
Section: Introductionmentioning
confidence: 99%
“…The growth and metastasis of a tumor depends on its own vascular network. Apart from the vessel tunnels, which are lined with endothelial cells, Maniotis et al found a new microcirculation mechanism: channels are externally lined with tumor cells, with no endothelial cells in human melanoma [5]. This phenomenon has been termed vasculogenic mimicry (VM).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, activation of p38MAPK in primary tumors has been revealed to contribute to EMT [34], which was a biological process of the lineage transition between epithelium and mesenchyme with invasive capacities [36]. To be specific, this process included the gradual loss of some features of epithelial cells (like the deletion of E-cadherin), the loss of cellular adhesion, and the acquirement of some new features (like the increase of mesenchymal cell marker proteins, vimentin and N-cadherin) [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a frequent behavior which can enhance cancer cell migration and invasion [27, 28]. To determine the effect of ATP and emodin on EMT of A549 cells, we examined expression of mesenchymal markers fibronectin, Snail and epithelia marker E-cadherin.…”
Section: Resultsmentioning
confidence: 99%